FIRST REPORT ON FIBRINOLYTIC AND THROMBOLYTIC ACTIVITY OF EUTYPHOEUS GAMMIEI AN EARTHWORM SPECIES COLLECTED FROM TRIPURA, NORTHEAST INDIA - Debnath, Madhusudan; Saha, Susmita; Kumar Sil, Samir (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present investigation for the first time evaluated the in vitro fibrinolytic and thrombolytic activities of crude extracts from Eutyphoeus gammiei, native, large size earthworm of Tripura, Northeast, India. The present study was designed to evaluate the therapeutic use of the organism E. gammiei as a source of fibrinolytic and thrombolytic agent(s). Methods: The fibrinolytic activity was studied using by fibrin plate and zymography assays. Thrombolytic assay was carried out according to Prasad et al. (2006) using whole blood. Results: The results obtained clearly indicated E. gammiei as a potential source of fibrinolytic and thrombolytic agents. Both in fibrin plate assay and thrombolytic assay with whole blood, E. gammiei crude homogenate showed similar and close results in respect to that of streptokinase. Fibrin zymography also showed antifibrinolytic activity with producing clear bands. Dose and time dependency also is evident from the results. Conclusion: The results of the present study conclude that the studied earthworm species E. gammiei possessed profound fibrinolytic and thrombolytic activity on human blood and E. gammiei might prove to be useful alternative source for the development of new drugs for treatments involving blood coagulation and fibrinolysis.